2011
DOI: 10.1186/1472-6963-11-265
|View full text |Cite
|
Sign up to set email alerts
|

Community based service providers' perspectives on frequent and/or avoidable admission of older people with chronic disease in rural NSW: a qualitative study

Abstract: BackgroundFrequent and potentially avoidable hospital admission amongst older patients with ambulatory care sensitive (ACS) chronic conditions is a major topic for research internationally, driven by the imperative to understand and therefore reduce hospital admissions. Research to date has mostly focused on analysis of routine data using ACS as a proxy for 'potentially avoidable'. There has been less research on the antecedents of frequent and/or avoidable admission from the perspectives of patients or those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 19 publications
1
42
0
3
Order By: Relevance
“…These services often have long waiting lists and there are often considerable additional barriers to accessing services, sometimes specific to rural locations. 25,37 A limitation of our study is that we did not aim to explore social isolation and it was not discussed in depth in every interview. We acknowledge that in-depth exploration of social isolation within interviews would have yielded greater detail and insight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These services often have long waiting lists and there are often considerable additional barriers to accessing services, sometimes specific to rural locations. 25,37 A limitation of our study is that we did not aim to explore social isolation and it was not discussed in depth in every interview. We acknowledge that in-depth exploration of social isolation within interviews would have yielded greater detail and insight.…”
Section: Discussionmentioning
confidence: 99%
“…Our methods are described in greater detail in our previous paper. 25 The study was approved by the North Coast Area Health Services Human Research Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this gap in the health system was recently highlighted in an Australian study that also interviewed community based service providers. 24 Our study identified that pharmacists are ideally placed to address this disconnect in the health system by navigating (or signposting) consumers from two perspectives: to other health professionals in a clinical triage role and to non-government consumer health organizations, thereby providing a more holistic approach to care. This can be viewed as complementary to the pharmacist's current role in the provision of medication advice.…”
Section: Discussionmentioning
confidence: 99%
“…Semi-structured interviews were used, giving stakeholders the opportunity to express their opinion(s) and experiences 24 , enabling exploration of a number of areas: concerns related to the management of a chronic illness and medication use that community pharmacy could assist with, views of the current and future role(s) of community pharmacy and potential barriers in developing these role(s). An interview guide (Table 1) …”
Section: Methodsmentioning
confidence: 99%